Rehabilitation of a partial ear defect using silicone prosthesis by anatomical anchorage method - A case report - Kanathila, Hema; Pangi, Ashwin M (Indian Journal of Case Reports, 2018)
Restoration of congenital and acquired defects is an art and science in the field of maxillofacial prosthetics. Partial defect of the ear can leave tissue which may be adequate for supporting the prosthesis. Silicone prosthesis gives a simplified, cost-effective, and acceptable means of restoring the lost parts of the body to those who are reluctant to surgical reconstruction and other expensive treatment modalities. The aim of this article is to present and discuss a clinical case of acquired auricular defect managed by silicone prostheses by anatomical anchorage technique, which is easy to use and acceptable in appearance to the patient.